Antibacterial Activity Test of Indigenous Yeast from Sapodilla Fruit against Staphylococcus aureus and Escherichia coli - GEMILANG LARA UTAMA; MUTIARA NABILA; HENI RADIANI ARIFIN; ELAZMANAWATI LEMBONG; TITA RIALITA (Microbiology Indonesia, 2019)
The research aimed to identify indigenous yeast antibacterial activity from sapodilla fruit against Escherichia coli and Staphylococcus aureus, which conducted by experimental methods and followed by descriptive analysis. This study was done by the isolation of indigenous yeast, macroscopic and microscopic identification, yeast identification using RapID Yeast Plus System, antibacterial test by measuring the clear zone diameter, testing of pathogenic bacteria viability against indigenous yeast and identification of organic acid produced by yeast. The results of yeast isolation obtained 1 isolate (Saccharomyces cereviseae 1) from fruit and 3 isolates form sapodilla skin (S.cereviseae 2, Candida famata, and Pichia anomala) which had antibacterial activity against E. coli and S. aureus except C. famata isolates. Isolates with the largest antibacterial activity against E. coli and S. aureus based on the clear zone diameter were S. cerevisiae (2) isolates. The results of organic acid analysis by HPLC found that S.cerevisiae (2) isolate produced the highest organic acid namely acetic acid as much as 2.442 mg mL -1. Â  Key words : antibacterial, organic acid, sapodilla fruit, yeast